Back Cover: Synthesis and Properties of Semiconducting Bispyrrolothiophenes for Organic Field‐Effect Transistors (Chem. Eur. J. 20/2014). Issue 20 (12th May 2014) - Jones, Crystalann; Boudinet, Damien; Xia, Yu; Denti, Mitch; Das, Adita; Facchetti, Antonio; Driver, Tom G.
<x xml:space="preserve">Abstract</x> Semiconducting bispyrrolothiophenes for thin film organic field effect transistors were constructed from vinyl azides using transition‐metal‐catalyzed CH bond functionalization. Pictured is an AFM image of one of the polycrystalline bispyrrolothiophenes that exhibited good field effect transistor performance despite its amorphous nature. For more information see the Full Paper by A. Facchetti, T. G. Driver et al. on page 5938 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>